Ethnobotany of Medicinal Plants with Antimalarial potential in Northern Nigeria - Mahmoud, Abdulrahman Dogara; Labaran, Isah; Yunusa, Abdulkadir (Ethnobotany Research and Applications, 2020)
Background: Traditional medicinal plants with potentials have contributed significantly in the history and evolution of modern health care system. Plants with medicinal value remain the only way forward as they are gaining more acceptability and recognition all over the world. Resistance of the malarial parasite all over the world has initiated the need for the exploration of plant parts for the invention of promising antimalarial drugs. In order to achieve this, a prior knowledge of the medicinal plants is needed from the traditional medical practitioners and any other person utilizing plants for medicinal purposes. Methods: The study was carried out through the administration of open-ended questionnaires to the age group of 30 and above. No prior appointment was made to the informants. A total of 100 informants were interviewed. Results: This study revealed 21species of medicinal plants. Malvaceae family have the highest abundance. Only plants with 0.5 relative frequency of citation and above were also listed. Leaves accounted for 35% of the most utilized parts, while decoction and oral were the most utilized methods of preparation and utilization at 44% and 60% respectively. Scientific validation of the documented medicinal plants is paramount in order to confirm, identify and isolate the compound responsible for antimalarial activity. Conclusion: Findings from this study will help in the production of new anti-malaria drugs, development of herbal product for malaria treatments and conservation of the medicinal plants with malarial therapeutic value to avoid future oversampling. The study hence recommends further studies on the in vitro and in vivo studies of the plant parts. Keywords: Traditional Medicinal Knowledge, Medicinal Plants, Northern Nigeria